Edukasi Pertanian Urban Farming with Fun Learning Pada Anak Usia Dini di Tingkat Sekolah Dasar - Pranajaya, Eka; Susetyo, Dwinanto Priyo; Andriani, Neneng Yanti (Journal of Community Service and Society Empowerment, 2024)
The lack of interest of the easy generation in the agricultural sector where the majority of the younger generation prefers to work in offices and industries is now an important issue that must be a common concern to support the national food security program. This issue underlies the birth of the PKM theme, namely Urban Farming Agricultural Education with Fun Learning for Early Childhood at the Elementary School level. Implementation methods, observation and socialization, implementation of hydroponic plant cultivation, library revitalization, evaluation of results and outputs. The results of activities, being able to increase children's understanding of agriculture have the potential to foster interest in the agricultural sector, the implications of this habit can develop after they grow up to contribute to improving national food security. Library revitalization activities are also useful in an effort to increase students' reading interest and reading culture. Long-term output, the future young generation will be created as diligent and disciplined human resources, highly talented, have extensive knowledge with critical thinking, have a variety of relevant competencies needed according to the demands of the times, so that they can be absorbed by various industries in the era of the Industrial Revolution 4.0 (IR4.0) towards the era of society 5.0 in welcoming the 21st century which is required by technological advances that are thick with the era of change.